The Struggle for Social Justice in British Columbia: Helena Gutteridge, the Unknown Reformer - Howard, Irene (UBC Press, 1992)
Helena Gutteridge was a socialist and feminist whose vision helped to shape social reform legislation in British Columbia in the first decades of the twentieth century, and also one of the first women there to hold high public office." "She was born in England in 1879. A militant suffragist, tutored by the Pankhursts, she learned the politics of confrontation early. Emigrating to Vancouver in 1911, she found the suffrage movement there too polite and organized the BC Woman's Suffrage League to help working women fight for the vote. And she kept on organizing. As a journeyman tailor she was a power in her union local, and as the only woman on the Vancouver Trades and Labor Council - their 'rebel girl' - she championed the rights of workers and organized women to fight for themselves. In the 1930s, as a member of the feisty new political movement, the Co-operative Commonwealth Federation, she joined in the struggles of the unemployed for work and wages. Then, in 1937, as the first woman ever elected to Vancouver City Council, she led the fight for low-income housing." "As was typical for women of her class and time, Helena did not keep personal records, nor did organizational records exist to any extent. Irene Howard made it her task, over a period of years, to search out and assemble details of Helena's life and career, and to interview old comrades who knew Helena and the turbulent times in which she lived. Herself a miner's daughter, the author brings to her subject an affectionate regard and sympathy qualified by the larger view of the scholar and researcher. The result is a lively biography, shot through with humour and pathos, that pays homage to Helena Gutteridge and to many of the people who have been inspired by a cause and who have taught us about the politics of caring."–Publisher's description
OCLC: 29599226
Keywords: Biografie; Biographies; British Columbia; Feminists; Feminists British Columbia Biography; Femmes Activité politique Colombie-Britannique (Canada) Biographies; Femmes Activité politique Colombie-Britannique Biographies; Femmes en politique Colombie-Britannique Biographies; Femmes socialistes Colombie-Britannique Biographies; Femmes sociologues Colombie-Britannique (Canada) Biographies; Femmes sociologues Colombie-Britannique Biographies; Féministes Colombie-Britannique (Canada) Biographies; Féministes Colombie-Britannique Biographies; Gutteridge; Helena; Gutteridge; Helena 1879-1960; Gutteridge; Helena; (1860-1979); Gutteridge; Helena; 1879-1960; History; Labor unions; Labor unions British Columbia History; Labor unions Officials and employees; Labor unions Officials and employees British Columbia Biography; Syndicalistes Colombie-Britannique (Canada) Biographies; Syndicats Colombie-Britannique Fonctionnaires Biographies; Syndicats Colombie-Britannique Histoire; Women Political activity; Women Political activity British Columbia Biography; Women in politics British Columbia Biography; Women socialists; Women socialists British Columbia Biography; Women sociologists; Women sociologists British Columbia Biography